Analyzing the Distributional Impact of Reforms : Vol. 1: A Practitioner's Guide to Trade, Monetary and Exchange Rate Policy, Utility Provision, Agricultural Markets, Land Policy, and Education. - Coudouel, Aline; Paternostro, Stefano (World Bank Publications, 2005)
Annotation